MENINGKATKAN KEMAMPUAN MEMBACA KALIMAT SEDERHANA BAGI ANAK LOW VISION MELALUI MEDIA KARTU KATA - Yamir - Nurta (Universitas Negeri Padang, 2013)
The purpose of this study is: aims to determine the effectiveness of the use of media cards increase the ability to read words in simple sentences for low vision children in the class II SDLB Blind Payakumbuh.This research approach Reaserch Single Subject (SSR) in a design with low vision AB (X). Target size their behavior is